An econometric analysis of tourism demand : Japanese tourist expenditure in ASEAN - Wong, Ching Ming (2014)
Tourism is a large industry. However, most of the time, the focus on this industry stays in the western part of the world. Recently, rapid growth of the East Asian tourism market is seen to set a certain trend. Hence, this study is performed by using the Almost Ideal Demand System (AIDS) model to estimate the behaviour of Japanese outbound travellers, particularly in terms of their expenditure, in the ASEAN countries. The AIDS model was founded upon conventional economic theory, hence the preference over single equation models. The estimated parameters from the AIDS model permits eventual computation of a series of expenditure of price elasticity values. These elasticities express the preference of the Japanese travellers for different destinations and thus, they provide information to the policy makers of these countries who can then take steps to improve their tourism industries.